Beta-adrenoceptor responses to high doses of inhaled salbutamol in patients with bronchial asthma. - Lipworth, B J (1988)
1. Fourteen asthmatics (mean +/- s.e. mean baseline FEV1 62 +/- 6% of predicted) were given cumulative doubling doses of salbutamol by metered-dose inhaler as follows: 100 micrograms, 200 micrograms, 500 micrograms, 1000 micrograms, 2000 micrograms, 4000 micrograms. 2. Airways, tremor, haemodynamic and cyclic AMP responses were measured at each dose increment (made every 20 min). 3. There was a linear log dose-response relationship for each airways parameter (FEV1, VC, sGaw, FEF 50%). The plateau in the dose-response curve was not reached within our dose range. These changes were also mirrored in cyclic AMP responses. 4. There was a wide range in maximum airways response expressed in terms of absolute increase over baseline (95% confidence intervals: delta FEV1 667-1483 ml; delta VC 689-1695 ml; delta sGaw 0.92-4.50 s-1 kPa-1; delta FEF 50% 0.94-2.15 l s-1). Patients with a lower baseline showed a greater response in terms of percent increase in FEV1 (r = -0.83, P less than 0.001). There was however, no correlation between baseline airway calibre and the dose required for maximum bronchodilatation. 5. There were objective increases (mean +/- s.e. mean) in both heart rate (maximum delta HR of 14 +/- 5 beats min-1 at 4000 micrograms) and tremor power (maximum delta Tr of 115 +/- 44% at 2000 micrograms). These were not dose limiting side-effects as subjective symptoms were infrequent at higher doses. 6. Higher than conventional doses of salbutamol given by metered-dose inhaler may produce a distinct improvement in airways response without significant side-effects.(ABSTRACT TRUNCATED AT 250 WORDS)